The revolting body: Self-disgust as a key factor in anorexia nervosa. (October 2021) - Glashouwer, Klaske A.; de Jong, Peter J.
Abstract: In this article, we present a theoretical model that points to disgust-induced avoidance as a mechanism that can help explain the persistent and excessive food restriction in individuals with anorexia nervosa (AN). Disgust is characterized by intense negative feelings of revulsion and an overwhelming and irresistible urge to avoid potential disgust elicitors. When eating, or even the prospect of eating, elicits overwhelming feelings of disgust in individuals with AN, this could explain why food restriction persists even when someone is in a state of starvation. Following this model, disgust is elicited by the expected impact of food on the own body ("becoming fat") resulting in body-related self-disgust. We argue that limiting food intake may serve to avoid self-disgust. This implies that when self-disgust remains unchanged after treatment of AN, residual levels of self-disgust after treatment could make individuals vulnerable to relapse.